PUBLIC TRANSPORT SYSTEM ADMINISTRATION S.01 DEPOSITS IN LIGHT RECEIPTS USING VISUAL BASIC 6.0 PROGRAMMING LANGUAGES - Siti Aminah.; Elly Agustina. J, SKom, MMSI (Jurnal Sistem Informasi, 2006)
To assist owners of public transport vehicles in performing bookkeeping up to date aswell as processing revenue and deposit money in a computerized, inspire writers tocreate a Visual Basic-based Administration System, so that subsequent data obtainedcan be processed as quickly as possible and easy to be revised in case of input errorsor mistakes calculating profits.The purpose of writing in making this system in order to familiarize the public in theuse of everyday on living computer, especially the public transport vehicle owners sothey would not hesitate in the use of computers in administrative process of moneyremittance receipts.